Desarrollo de una red local de sensores inalámbricos para un proceso de control de motores AC enlazados a un sistema IOT.. - Espin Pallango, Yessenia Cecibel (2023)
The main objective of this research is the design of a network of traditional sensors, which have been repowered through Wi-Fi access boards so that they can collect and transfer data on the parameters of the three-phase motor wirelessly, managing to integrate cutting-edge technologies that allow visualization remotely the correct operation of the engine in real time. The development process ranges from the collection of information, network and PCB design for the adaptation of the data collection cards coupled to the speed, frequency, voltage and current sensors of the motor to the configuration, programming and commissioning. operation of the data acquisition system that collects, processes the information and exports it to the Ubidots platform where it can be viewed from various devices such as computers, Smartphones and tablets. The validation of the wireless sensor network was carried out through rigorous experimental tests with the use of tools such as voltmeters, ammeters, tachometer and network analyzer, with the purpose of demonstrating the effectiveness and precision of the proposed system. In addition to the tests on the sensors and monitoring platforms, several analyzes of the behavior of the engine were established, such as its starting at different configurations, the speed transmission ratio was verified because the engine that is monitored has a gearbox. speed reducer and finally reaction tests are carried out in data acquisition and monitoring by varying certain parameters with a frequency converter. In conclusion, the development of this research provides a real-time monitoring system of the parameters of a three-phase motor in such a way that it opens several possibilities of use, including monitoring the operation of the motor from mobile devices and performing analysis of the parameters in operation to perform preventive maintenance and avoid unforeseen stoppages of the process.